Pre-donation Deferral Pattern of Allogeneic Blood Donors: An Analysis from a Developing Country - Sadia Sultan, Samar Abbas Jaffri, Syed Mohammed Irfan, Sheeza Nadeem, Mohammad Amjad Baig (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Pre-donation donor screening is a crucial step in ensuring the safety of both blood donors and recipients. Donors who do not meet predetermined criteria are temporarily or permanently deferred. Aim: To assess the patterns and prevalence of deferrals at our institution. Study design: Prospective study Place and duration of study: Karachi Tertiary Care Hospital, Karachi from 1st January 2014 to 31st December 2015. Methodology: Thirty six thousand, nine hundred and fifty four potential donors presented themselves, 33853 were selected and 3101 were excluded. Blood donors’ demographic information was stored in the blood bank’s database, and secondary measures such as the type of deferral (permanent/temporary) and reasons for deferral (donor or patient safety) were evaluated. Results: The majority 2663(7.20%) of donors were deferred due to complete blood count, followed by medical history 264(0.71%) and examination findings 174(0.47%). The majority of donors (96%) were temporarily deferred, while only 3.9% were permanently deferred. Low haemoglobin counts were the most frequent cause of treatment delays (78.8%), followed by hypertension (3.64%) and a history of medication usage (1.32%). Donor safety accounted for the majority of donor rejections (91.5%), while recipient safety accounted for 8.41%. Conclusion: The majority of donors were deferred due to abnormality in the profile of blood count mainly low hemoglobin level. The low hemoglobin counts were the most frequent cause of treatment delays, followed by hypertension and a history of medication usage. Only small numbers of donors were permanently deferred. Keywords: Blood donor, Deferral, Permanent, Temporary